2009
DOI: 10.1001/archgenpsychiatry.2008.509
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Electronic Diary Reports of Cue Exposure and Mood in the Hours Before Cocaine and Heroin Craving and Use

Abstract: Context In Ecological Momentary Assessment (EMA), participants electronically report their activities and moods in their daily environments in real time, enabling a truly prospective approach to the study of acute precipitants of behavioral events. EMA has greatly enhanced the study of tobacco addiction, but has rarely been attempted in individuals with cocaine or heroin addiction. Objective To prospectively monitor the acute daily-life precipitants of craving for, and use of, cocaine and heroin. Design Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
223
4
3

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 267 publications
(243 citation statements)
references
References 29 publications
(24 reference statements)
12
223
4
3
Order By: Relevance
“…Indeed, even after a period of abstinence, dependent individuals remain vulnerable to stress and other craving-inducing stimuli [10], which, in turn, leads to intense physiological responses and various negative feelings such as anger and sadness [11]. Real-time daily monitoring of craving and drug use has shown that craving reliably predicts relapse among dependent individuals [9,[12][13][14][15]. The data suggest that improving the treatment of craving could not only help prevent relapse, but could also reduce patient distress on the emotional, cognitive, and physiological levels.…”
Section: Overview Of Addiction and Current Treatment Challengesmentioning
confidence: 99%
“…Indeed, even after a period of abstinence, dependent individuals remain vulnerable to stress and other craving-inducing stimuli [10], which, in turn, leads to intense physiological responses and various negative feelings such as anger and sadness [11]. Real-time daily monitoring of craving and drug use has shown that craving reliably predicts relapse among dependent individuals [9,[12][13][14][15]. The data suggest that improving the treatment of craving could not only help prevent relapse, but could also reduce patient distress on the emotional, cognitive, and physiological levels.…”
Section: Overview Of Addiction and Current Treatment Challengesmentioning
confidence: 99%
“…BinDhim et al, 2014;Borland et al, 2013;Bricker et al, 2014;Buller et al, 2014;Haug et al, 2014;Hertzberg et al, 2013;Kirchner et al, 2013;Meredith et al, 2014;V. Patel, Nowostawski, Thomson, Wilson, & Medlin, 2013;Ploderer et al, 2014;Reitzel et al, 2014; Whittaker, 2011) Alcohol 12 (34.3%) (Bendtsen & Bendtsen, 2014;Dulin et al, 2014;Gajecki et al, 2014;Gamito et al, 2014;Haug et al, 2014;Kauer, Reid, Sanci, & Patton, 2009;Matsumura, Yamakoshi, & Ida, 2009;McTavish et al, 2012;Renner, 2012;Yu et al, 2012) Heroin 2 (5.7%) Epstein et al, 2009) Cocaine 1 (2.9%) (Freedman, Lester, McNamara, Milby, & Schumacher, 2006) General 3 (8.6%) (Campling, 2011;Ingersoll et al, 2014; Bendtsen & Bendtsen, 2014;BinDhim et al, 2014;Borland et al, 2013;Bricker et al, 2014;Buller et al, 2014;Dulin et al, 2014;Hasin et al, 2014;Haug et al, 2014;Ingersoll et al, 2014;Ploderer et al, 2014;Renner, 2012;Whittaker, 2011;Yu et al, 2012) Relapse prevention 3 (8.6...…”
Section: Discussionunclassified
“…Over half of the studies provided external support resources for participants, through either clinical treatment as part of the study Epstein et al, 2009;Ingersoll et al, 2014;McTavish et al, 2012), personal care or online interactive resources . However, almost half of the studies did not provide any resources or clinically relevant information for users.…”
Section: Communication Of Clinical Informationmentioning
confidence: 99%
See 2 more Smart Citations